PEMETAAN LAHAN PERTANIAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFI (SIG) TERHADAP TINGKAT KETAHANAN PANGAN DI KABUPATEN INDRAMAYU - Syaripulloh Syaripulloh; Imam Munandar; Iwan Purwanto; Masruroh Masruroh (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. Meeting the needs of the diverse agricultural sector from various agricultural subsectors is a challenge for the government at this time, mapping of food security must be applied to overcome these problems. As for the indicators of the level of food security according to the FSVA (A Food Security and Vulnerability Atlas) of Indonesia 2015, live below the poverty line, Percentage of villages with inadequate access to links, Percentage of households without access to electricity, Percentage of women over 15 years who cannot read or write, Percentage of households without access to clean water, Percentage of villages with distance greater than 5 km from health facilities, Toddlers with poor nutrition, Life expectancy at birth, this must be fully supported by various parties. The role of GIS applications in the analysis of food security levels is in the processing of data indicators / parameters of the level of food security overlapped into a map of food security levels. The purpose of this study was to analyze the dominant factors of food security parameters that affect the level of food security in Indramayu Regency.Abstrak. Pemenuhan kebutuhan dari sektor pertanian yang beranega ragam dari berbagai subsektor pertanian menjadi tantangan pemerintah saat ini, pemetaan ketahanan pangan harus diterapkan guna mengatasi masalah tersebut adapun indikator tingkat ketahanan pangan menurut FSVA (A Food Security and Vulnerability Atlas) of Indonesia 2015 adalah, Persentase penduduk yang hidup di bawah garis kemiskinan, Persentase desa dengan akses penghubung yang kurang memadai, Persentase rumah tangga tanpa akses listrik, Persentase perempuan di atas 15 tahun yang tidak dapat membaca atau menulis, Persentase rumah tangga tanpa akses ke air bersih, Persentase desa dengan jarak lebih dari 5 km dari fasilitas kesehatan, Balita dengan gizi buruk, Angka harapan hidup pada saat lahir, hal ini harus didukung sepenuhnya oleh berbagai pihak. Peran aplikasi SIG dalam analisis tingkat ketahanan pangan yaitu dalam pengolahan data indikator/parameter tingkat ketahanan pangan yang ditumpang susunkan (overlay) menjadi peta tingkat ketahanan pangan. Tujuan penelitian ini untuk menganalisis faktor dominan dari parameter ketahanan pangan yang mempengaruhi tingkat ketahanan pangan di Kabupaten Indramayu.